Lived experiences for individuals with cystic fibrosis who have undergone lung transplantation: a qualitative study - Ulrika Skogeland; Isabelle de Monestrol; Terezia Pincikova; Tove Godskesen (BMC Nursing)
Abstract Background Cystic Fibrosis (CF) significantly affects the respiratory system, often requiring lung transplantation in advanced stages. This life-saving procedure presents substantial challenges and uncertainties. While there is existing research on support and information needs post-lung transplant from various perspectives, this study aims to specifically address the unique experiences and challenges faced by individuals with CF during both the pre-transplant and post-transplant periods. Methods Twenty-three lung-transplanted individuals with CF participated in this exploratory qualitative study. Data was collected through individual semi-structured interviews and analyzed using inductive content analysis. Results Participants faced physical and mental challenges, including fatigue, depression, and anxiety. The waiting period involved isolation, dependence on family, and guilt. Post-transplant, they dealt with relief but also severe pain and adjusted to a new identity. Participants highlighted the importance of taking immunosuppressive medications as prescribed, even though the regimen was complicated and these medications had side effects. Participants stressed the need for earlier and more open dialogue with healthcare professionals and better emotional preparation for the transplant process, including preparedness for pain and previously inadequately addressed concerns such as depression and anxiety. Conclusions This study underscores the significant physical and emotional challenges individuals with CF face during lung transplantation, highlighting the need for comprehensive, person-centered care. Psychological support, effective post-transplant pain management, and early palliative care may be beneficial approaches to improve the patient experience. Nurses can play a pivotal role in this process by ensuring clear communication, managing pain, educating patients on immunosuppressive regimens, and advocating for holistic care.